Kesinambungan fiskal dan estimasi fiscal reaction function Indonesia tahun 1977-2017 - Akhmad Solikin; Hilda Choirunnisah (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2019)
This study aims to identify whether Indonesian fiscal condition in 1977–2017 is sustainable as measured by the government responses to debt burden. Studi on fiscal sustainability is very important since failing to identify its occurrence and determinants will detrimental to fiscal and macroeconomic policy. This study uses Auto-Regressive Distributed Lag – Error Correction Mechanism (ARDL-ECM) to estimate short-term and long-term fiscal reaction functions. The result shows that in the long-term the government responds an increase in debt burden by increasing its primary balance and thus it confirms the existence of fiscal sustainability. Furthermore, by estimating fiscal reaction function this study finds that in the long run exchange rate and Asian Financial Crisis in 1998 have significant effects on primary balance; while in the short run real exchange rates, 1998 economic crisis, and commodity prices affect the primary balance.